The Swiss Debt Brake - Has It Been a Success? - Tobias Beljean; Alain Geier (Swiss Journal of Economics and Statistics, 2013)
This paper describes how the Swiss fiscal rule at federal level has fared since it was introduced in 2003. Generally speaking, the rule has modified the budget process and led to a better implementation of fiscal policy objectives. It is argued that the most important factor is the existence of a binding ceiling for expenditure. The design of the mechanism is important in setting the right incentives. A basic feature of the rule is its simplicity and transparency. It is argued that an increase in sophistication would eliminate this advantage without guaranteeing preferable outcomes. It appears that the rule has contributed to a substantial reduction in nominal debt. This outcome has occurred against the backdrop of a favourable economic situation (which was not anticipated) and is primarily attributable to an underestimation of both revenues and economic growth. Nominal debt reduction may not materialise to the same extent under different circumstances. It appears that systematic underspending with respect to the budget leads to a bias towards budget surpluses. In addition, there has been no visible reduction in budget quality, and the fiscal policy stance as measured by the change in the cyclically adjusted budget balance has been appropriate given the prevailing economic conditions. While some design features may be debatable, the overall rules-based approach to fiscal policy has been successful.
Keywords: H6; 330; debt; debt brake; fiscal rules; Switzerland